IDENTIFIKASI FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA WANITA PADA PEKERJAAN KONSTRUKSI - F, Fahirah; Fadjar, Adnan; Wahliana, Sri (Jurusan Teknik Sipil Universitas Tadulako, 2017)
Understanding and knowledge of the important factors, either positive or negative, that influencing female workers on construction job can be used to prepare a strategy to reduce inefficiency and to increase effectiveness of the project performance in order to reduce cost overrun and schedule delay in construction project. The aim of this study is to understand the most influential factors that affect the female workers’ productivity on the construction job. This study uses Relative Rank Index (RRI) method to determine the most influential factors that affect the female workers’ productivity on the construction job and this study also uses Spearmans Rank correlation method to find out the significance of the hypothesis of the associative influencing factors. Data collecting is done by literature study, questioners, and interviewing construction experts. The study results show that based on the contractors’ perception, the most influential factors that affect the female workers’ productivity on the construction job are age, salary, working permit, and family commitment. There is a good correlation between family commitment factor and age, salary and working permit factors.